Painful and non‐painful diabetic polyneuropathy: Clinical characteristics and diagnostic issues. Issue 5 (29th July 2019) - Gylfadottir, Sandra Sif; Weeracharoenkul, Danita; Andersen, Signe Toft; Niruthisard, Supranee; Suwanwalaikorn, Sompongse; Jensen, Troels Staehelin
Abstract : The present review addresses the clinical characteristics of painful and non‐painful diabetic polyneuropathy and the possibilities for diagnosing these conditions. As the majority of patients with type 2 diabetes are treated in general practice, we focused on proposals for simple assessments of diabetic polyneuropathy outside specialized hospital clinics. Abstract: Diabetic neuropathy (DN) is a common complication of diabetes and can be either painful or non‐painful. It is challenging to diagnose this complication, as no biomarker or clear consensus on the clinical definition of either painful or non‐painful DN exists. Hence, a hierarchical classification has been developed categorizing the probability of the diagnosis into: possible, probable or definite, based on the clinical presentation of symptoms and signs. Pain is a warning signal of tissue damage, and non‐painful DN therefore represents a clinical and diagnostic challenge because it often goes unnoticed until irreversible nerve damage has occurred. Simple clinical tests seem to be the best for evaluation of DN in the general care for diabetes. Screening programs at regular intervals might be the most optimal strategy for early detection and interventions to possibly prevent further neuronal damage and to lower the economic burden of this complication.